2016
DOI: 10.12707/riv16019
|View full text |Cite
|
Sign up to set email alerts
|

Risky sexual behavior and knowledge of STIs/AIDS among university health students

Abstract: Background: Risky sexual behaviors are associated with the number of sexual partners, and non-use of condom, among other factors. Objective: To identify the profile of health students attending a higher education institution, according to demographic and sexual characteristics. Methods: This is a prospective, cross-sectional and descriptive study with a quantitative approach using a sample of 819 university health students. We used a questionnaire in order to obtain information on the students' demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
17

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 11 publications
1
15
1
17
Order By: Relevance
“…These data are found in the traditional literature. Furthermore, considering that the frequency of STI was significantly high in this study, sexual intercourse with several partners and homosexual relationships are generally considered as risk factors for the transmission of STI/HIV [27]. Although these data were also found in the studies of Benzaken et al and Borges, the first study conducted in the Amazon reported that only 38.5% of the individuals who participated in the study have reported condom use [15].…”
Section: Discussionsupporting
confidence: 67%
“…These data are found in the traditional literature. Furthermore, considering that the frequency of STI was significantly high in this study, sexual intercourse with several partners and homosexual relationships are generally considered as risk factors for the transmission of STI/HIV [27]. Although these data were also found in the studies of Benzaken et al and Borges, the first study conducted in the Amazon reported that only 38.5% of the individuals who participated in the study have reported condom use [15].…”
Section: Discussionsupporting
confidence: 67%
“…The results of this study should be interpreted considering some limitations. YRBS is a self-report instrument with intimate questions, which can influence the accuracy of answers, as participants may lie or omit important information due to privacy concerns (Sales et al, 2016). The excessive number of items in the instrument may discourage students from responding reliably.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos participantes encontrava-se na faixa etária de 21 a 24 anos, eram do sexo feminino e se autodeclararam pardos, o que está em conformidade com resultados encontrados em outras pesquisas realizadas com estudantes universitários no Brasil e em outros países 9,12 .…”
Section: Discussionunclassified
“…Entretanto, uma parcela significativa informou que realizava práticas homossexuais e bissexuais. Estudos indicam que estudantes universitários homossexuais e bissexuais são mais vulneráveis a situações de risco 9,15 .…”
Section: Discussionunclassified
See 1 more Smart Citation